InfoPA: - Silva, Paula Abrante Lima da (2021)
Overcrowding in urgentandemergencyservicesis a problemaroundthe world, causingdissatisfaction for staff, patientsandreducingthequalityindicatorsofinstitutions. Thisstudysoughttoanalyzeorganizational processes, andthenseek a solutionto improve thequalityofurgentandemergencycare, thusaimingto improve communication betweenpatientandit’scompanion. Withthepopulationincrease, thedemands in theEmergencyCareunitsincrease, andtheemployees are ofteninsufficienttocarry out this communication, soInfoPA, whichis a software prototype, wasdevelopedandit’sobjectiveistoinformthecompanion, theplaceswherethepatientispassingthroughduringyourcare. For theinstitution, InfoPAprovidesreportsto help improve management.